A humanized anti-Toll like receptor 4 antibody Fab fragment inhibits pro-inflammatory responses induced by lipopolysaccharide through TLR4 in vitro and in vivo - Wenkai Zheng; Fang Xie; Shuping Si; Xi Xiong; Jing Xu; Chuanxia Yao; Cong Li; Jin Zhu; Ping Li; Binggang Cai; Maorong Wang (Journal of Infection in Developing Countries, 2025)
Introduction: Toll like receptor 4 (TLR4) and its co-receptor MD-2 recognize bacterial lipopolysaccharide (LPS), initiating responses to infections caused by Gram-negative bacteria. TLR4 also plays a role in various pathological processes, including viral infections and sterile inflammation. However, effective methods to inhibit LPS/TLR4-mediated inflammation remain elusive. This study aimed to evaluate the inhibitory effects of a constructed hTLR4-Fab on LPS-induced inflammation in both in vitro and in vivo settings.